PEMBERDAYAAN PEREMPUAN MELALUI KELOMPOK WANITA TANI DI LINGKUNGAN SUKORE JO (STUDI KASUS PADA KWT LESTARI) - Dina Lesmana; Syarifah Maryam; Rina Andriana (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
The agricultural program given to sustainable farmer women's groups is a form of empowering women in the Sukorejo Lempake environment, this empowerment obliges participation, creativity, and initiative at activities carried out by sustainable farmer women's groups and is expected to have a better influence. The purpose of this research was to know the form of empowerment, the level of participation, and the influence obtained by sustainable farmer women's groups.This research was to be conducted from July to September 2020. The location of research has been determined purposive, namely in the environment of Sukorejo, Lempake Village, North Samarinda District, Samarinda City. The sampling method used was purposive sampling and was carried out by means of a census. The respondents in this research amount to 20 people, the method of analysis used is a descriptive qualitative method and the descriptive method uses a Likert scale.The results of this research showed that the program empowerment is given to sustainable farmer women's groups, namely training programs and processing practices in horticultural product agricultural, farm extension programs, entrepreneurship training, and participation in processed product exhibitions.The rate participation members of the Lestari farmer women's group the indicator of routine monthly meetings included high category with an average score of 10.78, the meetings indicator/extension agricultural were in the high category with an average score of 13.10, and the indicators training program were in the high category with an average score of 15.73. Overall with an average score of 39.61, it was in the high category.The influence on the sustainable farming women’s group in implementing agricultural extension program provided includes to income of the women farmer group, the role in the women’s farmer group, participation in the women’s farmer group, the knowledge and insight before and after joining the Lestari farmer women’s group was able to give a more good impact.The conclusions of this research showed that the participation of the sustainable farmer women’s group with an average score of 39.61 was in the high category and the influence obtained by the Lestari farmer women's group on the extension program seen from before and after joining with a sustainable farmer women’s group was able to have an influence towards better.